ANALISIS JALUR EVAKUASI KESELAMATAN DAN KESEHATAN KERJA (K3) PADA GEDUNG UNIVERSITAS MPU TANTULAR LANTAI 1–8 DAN DARI LANTAI 8–1 - Edison Hatoguan Manurung; Berlin P Sitorus; Retno Indriyati Kusuma Wardani; Sitti Wardiningsih; Franka Hendra Sukma; Betman Dasuha Purba; Yoel Gracio Bani; Hari Purnama; Jerry Eduard Efruan; M. Andi; Rahayu Clara Irawan; Muhammad Rivai; Sovian Harianja; Muhammad Hidayah; Resky Rafiatul; Muhammad Daffa; Pramudyo Ginanjar (SINERGI : Jurnal Riset Ilmiah, 2026)
Occupational Safety and Health (OSH) is an essential aspect in the management of multi-storey buildings, particularly in emergency situations such as fires, earthquakes, or other hazardous events. One of the key elements in implementing OSH is the availability of safe, clear, and accessible evacuation routes for all building occupants. This Community Service Program (Kuliah Kerja Nyata/KKN) aims to analyze the Occupational Safety and Health (OSH) evacuation routes in the Universitas Mpu Tantular building, which consists of eight floors, focusing on evacuation routes from the 1st to the 8th floor and from the 8th floor to the 1st floor. The method used in this activity was an observational and descriptive approach through direct field observations of evacuation routes, including emergency staircases, evacuation corridors, exit access, and evacuation signage. The results show that the Universitas Mpu Tantular building is equipped with evacuation routes that can be used during emergency conditions. However, several aspects still require improvement, such as the visibility and consistency of evacuation signage on each floor, potential obstacles along evacuation corridors, and the optimization of emergency lighting. This KKN activity contributes to increasing awareness and preparedness regarding Occupational Safety and Health (OSH) implementation through the evaluation of evacuation routes to enhance the safety of building occupants